Outcome of Acute Kidney Injury (AKI) Patients in the Intensive Care Unit of Enam Medical College & Hospital During the Period of July 2018 to May 2019 - Khanam, Easnem; Rahman, Shamimur; Islam, Ashraful; Rahman, Nelufa Tahera (Journal of Enam Medical College, 2023)
Background: Acute kidney injury (AKI) is a public health issue associated with multiple clinical conditions which may occur due to slight elevation in serum creatinine to anuric renal failure with electrolytes and acid-base imbalance, chronic kidney diseases, end-stage renal diseases, impaired innate immunity associated with higher infection rate, and increased duration of hospital stay with higher cost. Sometimes severe AKI patients may need intensive care support and renal replacement therapy. Severe sepsis is the most common cause of ICU admission. Materials and Methods: This observational study was conducted during the period of July 2018 to May 2019 in the Department of Anesthesiology and Intensive Care Unit of Enam Medical College & Hospital, Savar Dhaka. A total of 87 AKI patients were selected among which 48 were male and 39 were female. Acute kidney injury was selected with an increase in serum creatinine >0.3 mg /dL within 48 hours or ≥1.5 mg /dL from the base line within prior 7 days or urine volume <0.5mL/kg/hour. The last recorded lowest value or value within 24 hrs before admission was considered as baseline S. creatinine. Staging was done according to the KDIGO classification. Chronic Kidney Diseases (CKD) patients and acute on chronic kidney diseases patients aged <18 years were excluded from our study. Results: Highest age group was between 41 to 60 years. According to KDIGO definition 27.58% fell in stage-I, 39.8% in Stage-II and 33.33% in Stage-III. Hypertension (34.48%) and diabetes (24.18%) were found common co-morbid conditions. The most common indication for admission in ICU was septicemia (21.83%). Other causes include pneumonia and other respiratory illness (18.39%), gynae and obstetrical cases (16.09%) AGE (acute gastroenteritis) 13.79%, poisoning 9.19%, polytrauma 8.0%, cardiac diseases 6.89%, cerebrovascular diseases 3.44%, malignancy 2.29%. Total 62.06% (54) patients needed ionotropic support, 55.17% (48) needed artificial ventilation. 26.4% patients needed renal replacement therapy (8.04% HD, 12.64% SLED, 5.74% CRRT). Finally, 66 (75.86%) patients survived among which 59 (67.81%) recovered completely from AKI, 7 (8.04%) turned into CKD and 21 (24.13%) expired. Conclusion: Early detection and extensive ICU management may lead to full recovery of renal function which ultimately reduces adverse outcomes, renal replacement therapy and AKI-related morbidity and mortality. J Enam Med Col 2021; 11(1): 24-33